Wages and Establishment Size - Swimmer, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1978)
The author examines some of the more prominent research in the light of their author symethodologies and then, using current wage-size data, illustrates that size, per se, is not a determinant of wages; other factors interacting with size can produce higher wages, but do not necessarily have to do so.